Age-Specific Prevalence of Anal and Cervical Human Papillomavirus Infection and High-Grade Lesions in 11 177 Women by Human Immunodeficiency Virus Status: A Collaborative Pooled Analysis of 26 Studies. (23rd March 2022) - Wei, Feixue; Xia, Ningshao; Ocampo, Rebeca; Goodman, Marc T; Hessol, Nancy A; Grinsztejn, Beatriz; Ortiz, Ana P; Zhao, Fanghui; Kojic, Erna M; Kaul, Rupert; Heard, Isabelle; Morhason-Bello, Imran O; et al.
Abstract: Background: Age-specific data on anal, and corresponding cervical, human papillomavirus (HPV) infection are needed to inform female anal cancer prevention. Methods: We centrally reanalyzed individual-level data from 26 studies reporting HPV prevalence in paired anal and cervical samples by human immunodeficiency virus (HIV) status and age. For women with HIV (WWH) with anal high-grade squamous intraepithelial lesions or worse (HSIL+), we also investigated concurrent cervical cytopathology. Results: In HIV-negative women, HPV16 prevalence decreased significantly with age, both at anus (4.3% at 15–24 years to 1.0% at ≥55 years; ptrend = 0.0026) and cervix (7.4% to 1.7%; ptrend < 0.0001). In WWH, HPV16 prevalence decreased with age at cervix (18.3% to 7.2%; ptrend = 0.0035) but not anus (11.5% to 13.9%; ptrend = 0.5412). Given anal HPV16 positivity, concurrent cervical HPV16 positivity also decreased with age, both in HIV-negative women (ptrend = 0.0005) and WWH (ptrend = 0.0166). Among 48 WWH with HPV16-positive anal HSIL+, 27 (56%) were cervical high-risk HPV-positive, including 8 with cervical HPV16, and 5 were cervical HSIL+. Conclusions: Age-specific shifts in HPV16 prevalence from cervix to anus suggest that HPV infections in the anus persist longer, or occur later in life, than in the cervix, particularly in WWH. This is an important consideration when assessing the utility of cervical screening results to stratify anal cancer risk. Abstract : Age-specific shifts in HPV16 prevalence from cervix to anus suggest HPV infections may persist longer, or occur later in life, in the anus than cervix. This is an important consideration for using cervical screening results to direct anal cancer prevention.